Bartter-Like Syndrome as the Initial Presentation of Dent Disease 1: A Case Report - Qiaoping Chen; Yan Cao; Liyun Xu; Jingqi Liu; Xiaochuan Wu (Frontiers Media S.A., 2021)
Dent disease is a rare genetic disease characterized by low-molecular-weight proteinuria. Dent disease with Bartter-like syndrome is rare and can easily be misdiagnosed and mistreated. Herein, we report a case of Dent disease 1 with Bartter-like syndrome as the initial manifestation. The patient was admitted to The Second Xiangya Hospital of Central South University due to polydipsia, polyuria, and weakness of both lower limbs at 2 years of age. Laboratory tests showed that serum sodium, potassium and chlorine levels were low, while serum creatinine levels were normal. The calcium level in the urine was normal. The patient was initially diagnosed with Bartter syndrome, and despite medical interventions, he eventually developed chronic kidney disease stage 4 at 13 years of age. To determine the cause, the patient was recommended to undergo genetic testing, which showed a CLCN5 gene c. 941C > T mutation (p.S314L), and was finally diagnosed as Dent disease 1. The clinical manifestations of Dent disease are complex and diverse. For patients with atypical clinical manifestations or unsatisfactory therapeutic effects, genetic testing is recommended.